Jovens, projetos de vida e escola: relações e significados a partir da visão de estudantes do ensino médio de uma escola pública em Maceió - Araújo, Mariana Yezzi de (2013)
This research presents an explanation about the youth theme, going through their relationship with school and data on High School in Alagoas. Youth is understood here as a social category that must be investigated from the presupposition of diversity. It considers, therefore, that there are different youth and ways of being young. For such end, it is used as methodological instruments the implementation of questionnaires, interviews and a focus group formed with young people from a public school. Its objective is to investigate the connotations of school for public high school students from the city of Maceió and their relationship with their perspective of future. Furthermore, it is intended here to know about the young people´s projects of life, to realize what guides them and their strategies to accomplish them; to identify e discuss how the school is part of their everyday activities and discover the importance of school in young people´s projects and their perspectives for the future. The results found in the research show that young people have projects of life that include both professional aspects, such as attending a college they wish and getting a job, and personal aspects, like having a family, having their own house and being independent. The motivations for doing their projects are their family support and also the construction of a better life and the strategies to achieve their projects are basically finishing their studies and getting a job which will let them to attend a college and to succeed in their desired career. The school appears to young people as being of great importance to the achievement of their future plans, but they believe that it hasn´t helped them in the way they need for the accomplishment of it. For them, the school where they study seems to be very far from their reality and their needs, as young people, showing an instrumental and technical vision of teaching and not providing them the opportunity of being part, exposing their ideas and discussing themes that interest them. Still, young people understand their difficulties and ask for better quality in public education, starting with structural and materials issues, as well as better relationships between students, teachers, educational supervisors and principals. Therefore, it is considered that, from the data found about public education in Maceió and testimonies of young people, despite the school being considered essential to the accomplishment of their future projects, it didn´t provide experiences of a school that allows students to think criticality about their socio-cultural reality and gives them spaces for their youth experiences.